2009
DOI: 10.1103/physrevb.79.115212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Zn-vacancy–hydrogen complexes in ZnO single crystals: A challenge to positron annihilation spectroscopy

Abstract: A systematic study of various, nominally undoped ZnO single crystals, either hydrothermally grown ͑HTG͒ or melt grown ͑MG͒, has been performed. The crystal quality has been assessed by x-ray diffraction, and a comprehensive estimation of the detailed impurity and hydrogen contents by inductively coupled plasma mass spectrometry and nuclear reaction analysis, respectively, has been made also. High precision positron lifetime experiments show that a single positron lifetime is observed in all crystals investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
153
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 81 publications
19
153
1
Order By: Relevance
“…[12], but is significantly shorter than the mean positron diffusion length of about 100-200 nm typical for nearly defect-free semiconductors [13]. This can be explained by positron trapping in complexes consisting of Zn-vacancy associated with hydrogen atom (V Zn + H) detected in ZnO single crystal by positron lifetime spectroscopy [4]. Indeed, nuclear reaction analysis revealed that hydrogen introduced into ZnO crystal unintentionally during the crystal growth is present in concentration of %0.03 at.% and represents, thereby, the most important impurity in the virgin ZnO crystals [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12], but is significantly shorter than the mean positron diffusion length of about 100-200 nm typical for nearly defect-free semiconductors [13]. This can be explained by positron trapping in complexes consisting of Zn-vacancy associated with hydrogen atom (V Zn + H) detected in ZnO single crystal by positron lifetime spectroscopy [4]. Indeed, nuclear reaction analysis revealed that hydrogen introduced into ZnO crystal unintentionally during the crystal growth is present in concentration of %0.03 at.% and represents, thereby, the most important impurity in the virgin ZnO crystals [14].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical work by Van de Walle [3] showed that hydrogen is easily incorporated into ZnO lattice and should act as a shallow donor. Indeed hydrogen was found to be the most important impurity in high quality ZnO crystals grown by the state-of-art techniques [4]. Weber et al [5] clearly demonstrated that presence of hydrogen in oxygen deficient ZnO leads to red coloration of initially transparent crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Native defects such as oxygen vacancies or zinc interstitial are often assumed to be the origin of this, but the subject remains controversial [13]. Recent work indicates, for example, the existence of a huge amount of hydrogen (∼ 0.3%) in ZnO single crystals [14]. These impurities can influence the electronic properties of ZnO as has been observed several years ago [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the active defects could be related to the vacancy-hydrogen complexes recently found in ZnO crystals [14]. Also cation and anion vacancies which are double acceptors and donors in ZnO may contribute [17].…”
Section: Discussionmentioning
confidence: 99%
“…As hydrogen is a ubiquitous element and we have found recently that it is present in a large amount (of the order of 0.1 at.%) in a variety of ZnO materials [4], we suppose that it should also exist in zirconia. Indeed, first measurements using nuclear reaction analysis indicate that YSZ materials contain an appreciable amount of hydrogen [5] comparable to that in ZnO.…”
Section: Introductionmentioning
confidence: 99%